"Doing ASGM without mercury is like trying to make omelets without eggs". Understanding the persistence of mercury use among artisanal gold miners in Burkina Faso. Issue 133 (July 2022) - Bugmann, Anna; Brugger, Fritz; Zongo, Tongnoma; van der Merwe, Antoinette
Abstract: Researchers and policymakers are concerned with the uncontrolled use of mercury in artisanal and small-scale gold mining (ASGM). Despite the availability of alternative technologies, mercury is still the first choice to separate gold from ore on most ASGM sites. Taking the case of Burkina Faso, this mixed methods study contributes to understanding the continued use of mercury by analyzing the non-technical functions that mercury accomplishes. Applying a political ecology lens, we analyze the mechanisms that actors deploy to access benefits from ASGM and manage business-related risks, revealing dependencies on webs of power that govern the informal setting of the ASGM value chain from production to export. Our results challenge conventional wisdom about poverty-driven ASGM. We demonstrate that the sector is not simply propelled by jobless rural youth and poor farmers eager to make a lucky strike. Instead, the need of ASGM for prefinancing extraction made it as much the product of capital looking for lucrative investment. The business model of investors is based on prefinancing extraction, controlling access to market, and taking advantage of excess labor by shifting operational and financial risks upstream. In an entirely informal scheme of cascading prefinancing arrangements, mercury serves as a 'commitment and controlling device.' The provision of mercury guarantees that the financier can access the gold at the exact moment of recovery, regain the loan, and secure the return on investment. Phasing out mercury will remain a challenge as long as it is used as a social control device. Highlights: ASGM is increasingly dependent on investment to prefinance extraction. Capital is provided in an entirely informal manner by downstream actors in the value chain. Mercury serves as "commitment and controlling device" for investors to secure access to gold recovery. For capital providers prefinancing is a lucrative investment that gives control over upstream production and marketing. The "social control" function of mercury makes its replacement difficult if access to capital and markets are not addressed.